Early and mid-term outcomes of transcatheter closure of perimembranous ventricular septal defects using double-disc occluders - Ha, Nguyen Cong; Viet, Nguyen Lan; Nguyen, Huong Lan Thi; Hien, Nguyen Sinh; Hung, Nguyen Duc (Frontiers in Cardiovascular Medicine, 2025)
IntroductionVentricular septal defect (VSD) is a common congenital heart disease (CHD), accounting for 20–30% of all CHD cases. While surgical closure has been the gold standard for treatment, transcatheter closure has emerged as a less invasive alternative, particularly for perimembranous VSDs. This study aimed to evaluate the early and mid-term outcomes of transcatheter closure using a double-disc occluder device in a single-center Vietnamese cohort.MethodA prospective descriptive study was conducted at Hanoi Heart Hospital, Vietnam. A total of 81 patients aged ≥1 year or weighing ≥8 kg, with perimembranous VSDs and left-to-right shunting confirmed by Doppler echocardiography, underwent transcatheter closure. Procedural success, complications, and follow-up outcomes were assessed at 1, 3, 12, and 18 months post-procedure. Data were analyzed using SPSS 20.0.ResultsThe procedure achieved a success rate of 96.4%, with three failures due to large defects near the aortic valve causing significant aortic regurgitation or residual shunting. No mortality or severe complications such as device embolization or complete atrioventricular block were observed. Minor complications included transient arrhythmias (6.2%), femoral hematoma (8.6%), and mild allergic reactions to contrast agents (9.9%). At 18 months follow-up, residual shunting was minimal in 1.2% of patients, and no cases required surgical intervention.DiscussionTranscatheter closure of perimembranous VSD using a double-disc occluder device is a feasible, safe, and effective alternative to surgery with high success rates and low complication rates. This approach offers a promising solution for select patients, especially in resource-limited settings. Further multicenter studies are recommended to validate these findings and assess long-term outcomes.